A Microfluidic Device for Transfection of Mammalian Cells Using Adjustable Shear Stress - Cencen, Veronika (Université d'Ottawa / University of Ottawa, 2016)
Microfluidic technology is a rapidly progressing tool in biomedical engineering. Microfluidic devices are appreciated for their simplicity and production efficiency potential. Our research focuses on developing a microfluidic device capable of transfecting cells by applying shear stress to cause temporary membrane damage. The advantage of this physical method of transfection is the possibility of incorporating large molecules that cannot be inserted with more traditional chemical transfection methods, while avoiding the large fall in viability seen with other physical methods such as electroporation. Unlike previous groups, our device incorporates the use of microfluidic valves to allow tunability, and impedance sensing for cell membrane damage analysis. We achieve (95±5)% cell viability and up to (68±5)% efficiency in transfecting 3T3 cells with DNA-sized molecules. In future stages, we intend to add the device onto an existing cell-encapsulation device that is tasked with preparing therapeutic cells to be used in regenerative medicine applications.
Keywords: Microfluidics; Transfection; Impedance; Photolithograpy; PAH; FITC